(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The clay mineralogy of the Middle Miocene Nahan Formation of the type area, northwestern Himalaya, India has been investigated to understand the palaeoclimatic and palaeotectonic conditions in the frontal Himalayan terrain. The clay minerals were investigated by X-ray diffraction analysis. Study of the oriented aggregates of 35 representative clay samples of the Nahan Formation of the type area reveals that illite is the most dominant mineral followed by kaolinite, vermiculite and mixed layer clay minerals. The distribution of the clay minerals in the three measured sections of the Nahan Formation, namely the Shambhuwala – Nahan section, the Renuka – Nahan section and the Sataun – Rajban section is nearly uniform suggesting thereby the prevalence of similar sedimentation environments in the Himalayan foreland basin. The presence of illite and kaolinite suggests their derivation from crystalline rocks containing feldspar and mica as also from preexisting soils and sedimentary rocks. Further, the palaeoclimatic conditions were moderate. Vermiculite has been mainly formed by weathering and transformation of biotite. Warm and humid climatic conditions prevailed for a major part during the deposition of the detritus which favored weathering and transformation of minerals.